Evaluation of Proximate, TDS and pH Differences Among Argopuro Ground Coffee Varieties - Kusumaningtyas, Rizky Nirmala; Alwi, Annisa Lutfi; Ali, Fandyka Yufriza; Nuraisyah, Anni; Pratita, Dian Galuh; Anindita, Devina Cinantya (International Journal of Technology, Food and Agriculture, 2026)
Recent reports show a significant global rise in demand for ground coffee, highlighting a trend towards specialty brews. This interest has led to research on coffee's chemical properties that influence flavour. Key characteristics include proximate content, total dissolved solids (TDS), and pH levels. This study examines the chemical traits of ground Robusta and Arabica coffee from the Argopuro area, produced by Teaching Factory Coffes Processing, Politeknik Negeri Jember. This study used Robusta and Arabica coffee processed using natural, wet methods and were roasted at medium to dark levels. The analysis included key parameters: proximate analysis for total moisture and ash content (gravimetric method) and total fat content (Soxhlet method), additionally, pH measurements were taken with a pH meter, and total dissolved solids (TSS) were evaluated using a refractometer. Employing a non-factorial Completely Randomized Design (CRD), the study focused on the two coffee types: Arabica and Robusta Argopuro. Data analysis was rigorously conducted using an independent sample t-test. The findings clearly indicate that the type of coffee has a significant impact on the proximate content: water, ash and fat content and pH levels of the ground coffee, but not significant impact on TDS.